Intelligent trading/metering/billing system ITMBS-IV smart meter design - Goh, Benjamin Leck Wei. (2010)
Due to the fact of the limited amount and fast depletion of non-renewable energy sources from fossil fuel on Earth, we have to conserve our current supply. Another negative impact caused by these non-renewable energy sources is global warming. Thus, Singapore government is promoting the conservation of energy through various policies which include liberalising the electrical retail market and pricing the electricity consumption every half-hour. ITMBS is a system that the users in conserving electricity saving money and facilitate the selection of the electricity suppliers to utilize meter electricity sold to the power grid by the users consumer Previous work had been done by previous batch of students. Jennic wireless microcontroller will be replacing the PIC microcontroller and PLC modem. The Jennic microcontroller will be interfacing with DEM built from the chip ADE 7756 to obtain consumption information. The author is task to develop the hardware of the smart meter and integrate with Jennic via SPI Serial Peripheral Interface based on the chip manufactured by Citrus Logic CS5463 instead of ADE 7756, as it provide a better quality measurement of power compared to ADE 7756, moreover the latter chip is obsolete in the market. The report will start of by discussing the introduction and background of this project. Brief introduction on Smart Metering Operational Framework on chapter 2, chapter 3 will be Literature review that summarises the analysis and evaluation of the chip CS5463, the research work done by the author, setting it as base knowledge of the project, chapter 4 will be hardware prototype design, hardware setup, chapter 5 will explanation on the main source code of the software, chapter 6 is the failure milestone experience of the author and chapter 7 shows the connection setup of the energy meter with Jennic. Chapter 8 will be the conclusion of the report and the datasheet and the source code of the project will be placed at the appendix of this report.